PENERAPAN SANKSI PENENGGELAMAN KAPAL ASING PELAKU ILLEGAL FISHING OLEH PEMERINTAH INDONESIA (PERSPEKTIF HUKUM INTERNASIONAL) - Siti Munawaroh (MIMBAR YUSTITIA, 2019)
Indonesia is an archipelagic country which most of its territory consists of vast territorial waters (sea) and is geographically the largest archipelagic country in the world. The Indonesian Sea has an area of 5.8 million km2 consisting of; territorial sea with an area of 0.8 million km2, archipelago sea 2.3 million km2, and EEZ 2.7 million km2, and has 17,480 islands with a coastline of 95,181 km2, and has a very large and diverse fisheries potential. This research uses the normative study method of finding the rule of law, principles of law, and legal doctrine to answer legal issues in applying the sanctions of foreign vessels that do illegal fishing. The potential of fisheries is an economic potential that can be utilized for the future of the nation as a basis for national development. However, there are still irresponsible parties who take Indonesia's marine products illegally or commonly referred to as illegal fishing. Illegal fishing is a criminal act that can be subject to sanctions.